Frackman: Getting to the Core of Coal-Seam Gas - Dooley, Kath (2016)
Flammable water, mysterious illnesses, ruined land: coal-seam-gas mining has some pretty nasty associations. A recent documentary that looks at what fracking is doing to rural Queensland communities provides many opportunities for students to investigate both this important environmental issue and the film itself.